Do Public Health Interventions Crowd Out Private Health Investments? : Malaria Control Policies in Eritrea - Carneiro, Pedro (World Bank, Washington, DC, 2015)
It is often argued that engaging in indoor residual spraying in areas with high coverage of mosquito bed nets may discourage net ownership and use. This is just a case of a public program having perverse incentives. This paper analyzes new data from a randomized control trial conducted in Eritrea, which surprisingly shows the opposite: indoor residual spraying encouraged net acquisition and use. The evidence points to the role of imperfect information. The introduction of indoor residual spraying may have made the problem of malaria more salient, leading to a change in beliefs about its importance and to an increase in private health investments.